Usulan Perbaikan Kualitas dengan Metode DMAIC untuk Meminimalisasi Cacat Benang di bagian Twisting PT X - Indah S., Neneng Meiliana; Wawolumaja, Rudy (Zenit, 2013)
PT X is a spinning company which produces sewing thread. The company has some quality problems at twisting area, where defects are detected. To improve the quality performance in that area, DMAIC method is used . The result of the study and analysis reveals that the first priority of defect that has to be fixed is curly thread, then hairy thread, and last is the thread that has abnormal TPI. The research suggests some improvement proposals: the use of ultraviolet light sensor forthread, installation of automatic system at some parts of the machine, cooperation with raw thread suppliers and/or spare-part machine suppliers to look for solutions by collaborating with SISIR, the possibility of finding alternative suppliers, the use of the original spare parts, some training andmentoring how to maintain the machine for relevant staff and technicians , utilization of check-sheet form in work inspection which is to be filled, completed by operators and to be checked by chief operator, and the use of picture image of assembly thread line as a guide for operators.Keywords: Thread Defect, Quality, DMAIC, 5W+1H